PENERAPAN DISCOVERY LEARNING BERBANTUAN LABORATORIUM VIRTUAL DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS PADA ASPEK MERENCANAKAN PENELITIAN SISWA SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Science process skills are skills used by scientist to obtain knowledge products. Research planning is one of the important aspects of science processing skills and help improve students' mindsets through experimental activities so that they are able to develop their scientific skills. The purpose of this study is to describe the extent to which students' science process skills in research planning after applying the virtual laboratory-assisted discovery learning model to Newton's law material. There were 141 students who participated in the research conducted in class X MIPA in the even semester of the 2021/2022 academic year at SMA Negeri 2 Tualang, Kab. Siak, Prov. Riau. This research is a quasi-experimental research with a non-equivalent control group design involving two groups, namely the experimental group and the control group. Descriptively, the pretest of students' science process skills in both groups was categorized as very poor. The experimental group will be treated with the application of discovery learning assisted by a virtual laboratory and the control group using conventional learning. The percentage of students' research planning skills with conventional learning based on the posttest average score is 55 which is still in the poor category, while the research planning skills of students with virtual laboratory assisted discovery learning have increased to 89 and are in the very good category.Keywords: Discovery Learning, Science Process Skills, Virtual Laboratory, Research Planning